Design of bionic mole forelimb intelligent row cleaners - Jia, Honglei; Wang, Qi; Huang, Dongyan; Zhu, Longtu; Li, Mingwei; Zhao, Jiale (International Journal of Agricultural and Biological Engineering, 2019)
In Northeast China under no-till conditions the amount of maize stubble of the previous year's crop severely limit the quality of sowing operations by unstable operating depth of normal planter row cleaners. Thus, in this study, bionic mole forelimb intelligent row cleaners comprising of a cleaning device and a depth intelligent control system were designed. Via theoretical analysis, computer-based simulation, and test optimized design, the mechanism of bionic cleaners that possessed the forelimb motion morphology and the front claw toe structural morphology of moles was studied, the effects of structural parameters of bionic cleaners on the cleaning quality were clarified. Based on a pressure sensor, a depth intelligent control system was designed, which enhanced the depth stability of the cleaning devices. The types of bionic cleaners were identified by simulation on EDEM software. Then regression equations between different parameters and operation evaluation indices were established, and the optimal parameter combination was identified on Design-Expert software with a rotation radius of 150 mm and a motion deflection angle of 15.8°, at which the cleaning rate was 91.3%. Field tests under the optimal parameter combination showed that bionic cleaners outperformed normal planar cleaners, and the depth intelligent control system could efficiently improve the performance of the row cleaners. The straw cleaning rate of the bionic mole forelimb intelligent row cleaners under total straw mulching fields was 90.9%, which was 21.3% higher than that of normal cleaners, and the ground surfaces after operation satisfied the agricultural requirements of maize no-tillage sowing.Keywords: bionic mole forelimb, intelligent row cleaners, intelligent control systems, no-till sowing, corn production, residue managementDOI: 10.25165/j.ijabe.20191203.4408Citation: Jia H L, Wang Q, Huang D Y, Zhu L T, Li M W, Zhao J L. Design of bionic mole forelimb intelligent row cleaners. Int J Agric & Biol Eng, 2019; 12(3): 27–35.